FINANCIAL INFORMATION IN THE BUSINESS OF COMMERCIAL NAVIGATION - Pahlen Acuña, Ricardo (2013)
The aim of this paper is an analysis of the effects of the activity of commercial airline companies and that informed or should report in their financial statements. In recent times there has been a large increase in tourism. The World Tourism Organization says that among all economic activities, tourism is one of the fastest growing in recent years worldwide, and the trend is to remain so. The contributions generated by this activity are numerous and cover various fields: economic, social, cultural, environmental media, etc.. This leads to more and more countries using this industry in support of their development strategies. One wonders, if the above produce harmful components increases in the atmosphere causing climate change and also, if there are agents who are developing plans to avoid introducing new aircraft engine concepts regarding manufacture, operation and maintenance. Also, from the point of view of the accounting profession, we arise the question: What the airlines provide information in the financial statements on the impact produced on the environment caused by flight activity?